Blockchain data sharing scheme based on localized difference privacy and attribute-based searchable encryption - Tao FENG; Liqiu CHEN; Junli FANG; Jianming SHI (Tongxin xuebao)
Aiming at the problem that traditional cloud-based data sharing schemes rely on trusted third parties and only focus on data privacy protection or access control, a blockchain data sharing scheme based on localized difference privacy and attribute-based searchable encryption was proposed.The blockchain and cloud server were combined to store data chain by chain and provide efficient, reliable and tamper-proof data sharing.Firstly, the localization difference privacy was introduced to preprocess the shared data to protect the privacy of the data owner and resist the attack of the untrusted third party.Secondly, the searchable encryption technology and attribute-based encryption were combined to realize data privacy protection, support ciphertext retrieval, and provide fine-grained access control for shared data.Finally, the safety, the correctness proof, and the experimental analysis proves that the proposed scheme meets the safety objectives.